Contesting the Narrative of Colombian Violence - Mark Piccini (Journal of Contemporary Poetics, 2020)
Even though violence in Latin America varies a lot between and within countries, Colombia has long been seen as the epicentre of an intense kind of Latin American violence that appears fundamentally different from everyday antagonism in what is known as the West, the First World, or the Global North. Colombia has been paralysed for half a century by an undeclared civil war between government and anti-government forces, fought first against the backdrop of the Cold War, and then against the United States-led war on drugs. This article will discuss the Colombian writer Evelio Rosero, who challenges the tendency to look to his country for an exceptional Colombian violence. His short story “Brides by Night” and novel The Armies step back from the context of the Colombian conflicts to draw attention to gender violence. This article argues that violence against women is a universal concern, and that the way it is represented by Rosero contests narratives that confine violence to Colombia as a place of exception. Using the psychoanalytic theories of subjectivity developed by Jacques Lacan, Slavoj Žižek, and others, this article discusses how a similar libidinal investment in women and Colombians as Other confines both gender demographic and a racial demographic to a similarly precarious position. In a globalising world, it is not only counterintuitive, but unethical to imagine and, in so doing, reinforce patterns of marginalisation and violence. A collective effort to traverse the fantasy of otherness in different art forms and media is crucial.